As redes referenciais na construção de notas jornalísticas - Matos, Janaica Gomes (2018)
Our thesis focuses on the need to rediscuss the classical views around referential chains in Text Linguistics, to propose the notion of referential networks, more compatible with sociocognitive-discursive presuppositions, in reference studies, so to consider the parameters of the textual genre and the construction of recategorisations (referential progressions) applied to the newspaper note. Regarding the genres, we theoretically have support in Figueiredo (2003), author who proposes the models of rhetorical-compositional patterns of the subgenres of newspaper notes: news note, comment note and reported comment note, which we adapt as news note and opinative note and relate to the operation of the reference network categories in these subgenres, prototypically. As regards the observation of the interrelation between referents in recategorization, we have as theoretical contribution the works of Cavalcante, Custódio Filho and Brito (2014), which deal with the sociocognitive processes of reference, as well as Custódio Filho (2011), which suggests the schematic of the stages of (re) elaboration by which the referents textually pass, and also, by Cavalcante and Brito (2014), proposing authors of the frame of functions of the referential construction. Thus, we analyzed a total of forty (40) copies of online newspaper notes (twenty (20) news notes and twenty (20) opinative notes), in order to confirm a certain regularity between compositional elements of the subgenres and the construction of certain reference networks, in order to attend to the various functions in the generic structuring, thus providing a variety of information that entails changes (recategorizations) by adding and confirming, or even disconfirming data on the referents, all discursively interconnected. Such networks are thus organized in a complex network of interactions, constructed in various ways, explicit or not, in favor of central facts reported, or commented in these texts.